2021
DOI: 10.1186/s12879-020-05598-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing tuberculosis gene signatures in malnourished individuals using the TBSignatureProfiler

Abstract: Background Gene expression signatures have been used as biomarkers of tuberculosis (TB) risk and outcomes. Platforms are needed to simplify access to these signatures and determine their validity in the setting of comorbidities. We developed a computational profiling platform of TB signature gene sets and characterized the diagnostic ability of existing signature gene sets to differentiate active TB from LTBI in the setting of malnutrition. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…The TBSignatureProfiler was used to profile signatures; it contains functions for analyzing gene lists from pathways or signatures to determine the predictive value ( 24 ). Scoring methods used here were Gene Set Variance Analysis (GSVA) and single sample Gene Set Enrichment Analysis (ssGSEA).…”
Section: Methodsmentioning
confidence: 99%
“…The TBSignatureProfiler was used to profile signatures; it contains functions for analyzing gene lists from pathways or signatures to determine the predictive value ( 24 ). Scoring methods used here were Gene Set Variance Analysis (GSVA) and single sample Gene Set Enrichment Analysis (ssGSEA).…”
Section: Methodsmentioning
confidence: 99%
“…To assess the significance of the 12-marker signature in independent TB cohorts, we performed ssGSEA on published transcriptomic TB datasets 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 from the curated TBData R package ( Table S1 ). We observed higher enrichment scores in the active TB group, compared with either latent TB or healthy controls in all the transcriptomic TB datasets except one (GEO: GSE19444 ) ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…We compared the 12-marker signature with the other published gene signatures 12 , 28 , 29 , 32 , 33 , 34 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 from the TBSignatureProfiler R package 36 and published protein signatures 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 to investigate the overlap with the proteins of our signature ( Figure 4 C). VEGFA, IL-6, and IFN-gamma were identified in at least 2 other proteomic studies, 58 , 59 , 60 , 61 , 62 whereas CD274 (also called PD-L1) was observed in several published transcriptional signatures.…”
Section: Resultsmentioning
confidence: 99%
“…We then compared the 12-marker signature with the other published gene signatures from the TBSignatureProfiler R package (28) and published protein signatures to investigate overlap between protein and transcriptional signatures with the proteins of our signature (Figure 5C). VEGFA, IL6, and IFN-gamma were identified in at least two other proteomic studies (29)(30)(31)(32)(33), while CD274 (also called PD-L1) was observed in several published transcriptional signatures.…”
Section: Identification Of a New 12-protein Signature For Active Tb D...mentioning
confidence: 99%